ŚWIADCZENIE O TRAUMIE, KATASTROFIE, ZAGŁADZIE… W STRONĘ KARTOGRAFII POTENCJALNEJ - Madurowicz, Mikołaj (Prace Polonistyczne, 2024)
This article examines the ways in which trauma, catastrophe, the Holocaust, and other extreme existential experiences are (re)represented in various cultural texts – particularly literary and cartographic narratives. The first part addresses trauma’s inexpressibility, the impossibility of providing testimony to genocide, massacres, ethnic cleansing, and interrelated acts of organized violence. It explores how such dramatic situations are depicted in the visual arts (painting, photography, film), music, architecture, and the academia (especially history). The second part of the article explores methods of cartographic representation of trauma and extreme experiences. More specifically, it examines the techniques and ideological programme of post-representational cartography. The third part analyzes the literary testimony to the space of genocide in Podolia given by Leopold Buczkowski in Black Torrent (Czarny Potok). The novel presents a landscape of the multidirectional violence that took place in Brody in the Eastern Borderlands, by using experimental means of expression which suggest that the destruction of the world can only be depicted through a degraded, shattered, crippled language. The analysis of Buczkowski’s work helps answer the question posed in the fourth part of the article, which asks whether conventional cartography can “express the inexpressible”.